2021
DOI: 10.1038/s41467-020-20622-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling serum antibodies with a pan allergen phage library identifies key wheat allergy epitopes

Abstract: Allergic reactions occur when IgE molecules become crosslinked by antigens such as food proteins. Here we create the ‘AllerScan’ programmable phage display system to characterize the binding specificities of anti-allergen IgG and IgE antibodies in serum against thousands of allergenic proteins from hundreds of organisms at peptide resolution. Using AllerScan, we identify robust anti-wheat IgE reactivities in wheat allergic individuals but not in wheat-sensitized individuals. Meanwhile, a key wheat epitope in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…1A ). 14,17,18 The quality of the resulting ToxScan library was assessed via sequencing to a depth of 288-fold coverage. We detected 99.3% of the library peptides, and found them to be relatively uniformly represented ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A ). 14,17,18 The quality of the resulting ToxScan library was assessed via sequencing to a depth of 288-fold coverage. We detected 99.3% of the library peptides, and found them to be relatively uniformly represented ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13 PhIP-Seq with a library spanning the proteins of the Allergome database (“AllerScan”) has recently been used to profile allergic IgE antibodies and their modulation in response to wheat oral immunotolerance therapy. 14 While it would not be feasible to create a phage library that covers the millions of proteins expressed by the human microbiota, 15 we have designed and constructed a novel library to represent a set of environmental proteins more likely to elicit immune responses: the 14,430 diverse proteins with “toxin” or “virulence factor” included as keywords in the UniProt database. This PhIP-Seq library of 95,601 56-amino acid peptides is therefore a unique representation of the environmental “toxome”/ “virulome”, which we refer to here as the “ToxScan’’ library.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide phage display has also been applied to wheat allergies in a recent study. 36 Here, we showed that, together with saturation mutagenesis, AllerScan creates a high-resolution image of both IgG and IgE repertoires and can be used to track their evolution during immunotherapy for allergy. We propose that the detailed definition of both epitopes recognized by the antibodies of food-allergic subjects and epitopes that are not may have practical applications in future personalized allergen immunotherapy strategies.…”
Section: Discussionmentioning
confidence: 97%
“…Major wheat allergens that are well characterized include: ω−1, 2, 5 gliadin, α/β/γ-gliadins, the high molecular weight glutenin subunits (HMW-GS) and low molecular weight glutenin subunits (LMW-GS), β-amylase, α-amylase/trypsin/subtilisin inhibitor proteins, lipid transfer protein, chitinase, glyceraldehyde-3 phosphate dehydrogenase, triosephosphate isomerase, peroxidase, glutathione S-transferase, globulin-3, serpins, and α-purothionin (Cianferoni, 2016;Juhász et al, 2018). For detailed information on wheat allergens, and their IgE epitopes, readers are referred to these excellent articles (Denery-Papini et al, 2011;Matsuo et al, 2015;Monaco et al, 2021;Pahr et al, 2013). In general, the inherent factors affecting the allergenic potential of food proteins include the protein's structure, stability to gut digestion process, and the glycosylation patterns (Huby et al, 2000).…”
Section: Introductionmentioning
confidence: 99%